The Relationship between PPE Compliance and COVID-19 Incidence among Nurses at Muhammadiyah Pekajangan Hospital, Pekalongan Regency - Arofah, Siti; Izzah, Nur (Prosiding University Research Colloquium, 2022)
COVID-19 is a global pandemic that has become the worid’s attention. The Indonesia government has declared COVID-19 a National Disaster. As front – line health care providers, nurses have a high risk af being exposed to COVID-19. Compliance using personal protective equipment ( PPE ) is essential in preventing the transmission of COVID-19. Objective this study aims to determine the relationship between personal protective equipment compliance and the incidence of COVID-19 among nurses at Muhammadiyah Pekajangan Hospital. Sample this study involved all nurses at Muhammadiyah Pekajangan Hospital as many as 143 respondents ( Response rate 93 % ). Methods a descriptive correlative study with a cross – sectional approach was used. Data were collection using a self – protection compliance questionnaire. Data were analyzed by using chi – square. The results showed that most of the nurses aged 26 – 35 years ( 60.2 % ), female ( 66.9 % ), had a three years Nursing education ( 85 % ) with a working period of 5 years ( 76.7 ), and did not comply with the use of personal protective equipment ( 72.9% ) and had never been confirmed positive for COVID-19 ( p – value < 0.001; OR = 11.23 ). This study indicatet that nurses who comply with personal protective equipment have an 11 times chance of not experiencing COVID – 19. Conclusion compliance with the use of personal protective equipment is critical in preventing the transmission of COVID – 19 to nurses.